Anatomy of one service-oriented architecture implementation and reasons behind low service reuse. Issue 2 (June 2016) - Alkkiomäki, Ville; Smolander, Kari
Abstract This paper evaluates the promises of service reusability through an analysis of services implemented in a manufacturing enterprise. A total of 103 services implemented in the case enterprise are analyzed to understand the enablers and obstacles that have led to the reuse ratio of 13 %. The main identified enabler for reusable services was the capability to define the services as a part of reusable business concepts, which is aligned with some of the earlier studies on the adoption of service-oriented architecture in enterprises. The main reason for having overlapping services in the case enterprise was lagging migration of legacy services to use newer, reusable services. The results can be used to develop service engineering methodologies for better reusability, and the paper provides practical guidelines to help in the application of integration development efforts toward reusable services.